Effect of foot reflexology on neonates' clinical outcomes with hyperbilirubinemia undergoing phototherapy: A randomized controlled trial. Issue 2 (April 2023) - Badr, Eman Arafa; Ibrahim, Heba
Abstract: Background: Neonatal hyperbilirubinemia is the most common reason for neonatal admissions to the Neonatal Intensive Care Unit that can progress to critical levels. Foot reflexology therapy is one of the complementary alternative therapies that can help to upgrade neonatal clinical outcomes with hyperbilirubinemia. Aim: This study aimed to investigate the effect of foot reflexology on neonates' clinical outcomes with hyperbilirubinemia undergoing phototherapy. Design: A Quasi-experimental two groups research design was used to accomplish this study. Methods: This study was conducted at Neonatal Intensive Care Unit in Alexandria University Children's Hospital at Smouha, Alexandria on 60 full-term neonates with hyperbilirubinemia undergoing phototherapy, were randomly assigned to two groups Neonates of the control group were received only phototherapy for hyperbilirubinemia, While foot reflexology neonates received intervention on the gastrointestinal system zone for 20 min in the morning before feeding once daily for consecutive five days beside phototherapy. Results: foot reflexology neonates exhibited a decrease in total bilirubin level to 7.9000 ± 1.81545 on the fifth day compared to 10.1633 ± 1.77054 for the control group neonates. A decline in the mean duration of undergoing phototherapy for neonates in the foot reflexology group to 4.30 ± 0.466 on the contrary with 5.00 ± 1.017 days for the control group. Conclusion: Application of foot reflexology is effective in improving the full-term neonates' clinical outcomes with hyperbilirubinemia undergoing phototherapy. Thus, this non-pharmacological method is recommended as a supplement treatment for neonates with hyperbilirubinemia beside phototherapy.